2014
DOI: 10.1182/blood-2013-11-538819
|View full text |Cite
|
Sign up to set email alerts
|

SIRT1 prevents genotoxic stress-induced p53 activation in acute myeloid leukemia

Abstract: Key Points• SIRT1 is highly expressed in subsets of patients with acute myeloid leukemia harboring activating mutations in signaling pathways and is regulated at the protein levels.• Targeting SIRT1 sensitizes leukemic blast to tyrosine kinase inhibitor treatment or chemotherapy via restoration of p53 activity.SIRT1 is an important regulator of cellular stress response and genomic integrity. Its role in tumorigenesis is controversial. Whereas sirtuin 1 (SIRT1) can act as a tumor suppressor in some solid tumors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
84
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(89 citation statements)
references
References 48 publications
4
84
0
1
Order By: Relevance
“…Deacetylated p53 and SIRT1 overexpression can be detected by immunoblotting. 74,84 In cases of non-SIRT1-mediated deacetylation, HDAC and MDM2 inhibitors might be beneficial. wtp53 cytoplasmic sequestration, confirmed by immunocytochemical staining, 114 can be reversed by CRM1 inhibition.…”
Section: Targeting Dysfunctional Wtp53 In Amlmentioning
confidence: 99%
“…Deacetylated p53 and SIRT1 overexpression can be detected by immunoblotting. 74,84 In cases of non-SIRT1-mediated deacetylation, HDAC and MDM2 inhibitors might be beneficial. wtp53 cytoplasmic sequestration, confirmed by immunocytochemical staining, 114 can be reversed by CRM1 inhibition.…”
Section: Targeting Dysfunctional Wtp53 In Amlmentioning
confidence: 99%
“…Protein expression of SIRT1 is overexpressed in Ammad Ahmad Farooqi et al FLT3-ITD+-cells and regulated by FLT3 kinase activity. Genetic or chemical inhibition of SIRT1 remarkably enhanced p53 mediated apoptosis (Sasca et al, 2014). It has recently been persuasively revealed that ATM was not induced in irradiated HER2 silenced MCF-7 breast cancer cells (Yan et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…SIRT1 protein is stabilized by USP22, a deubiquitinase that is induced by c-MYC in FLT-ITD AML cells (Li et al, 2014). In addition, SIRT1 activity is further regulated by ATM-DBC1 in a FLT-ITD dependent manner (Sasca et al, 2014). Inhibition of SIRT1 sensitizes FLT-ITD AML stem/progenitor cells to tyrosine kinase inhibitor treatment, and may help improve management of this category of AML.…”
Section: Abnormal Proteinmentioning
confidence: 99%
“…SIRT1 protein expression is more consistently increased in AML samples, particularly those harboring FLT-ITD alteration. The change of SIRT1 mRNA is less consistent in certain AML subcategories from one to another study (Sasca et al, 2014;Li et al, 2014). Prognosis AML with FLT-ITD mutation has poor prognosis.…”
Section: Acute Myeloid Leukemiamentioning
confidence: 99%